Experimental identification of edge temperature ring oscillation and alternating turbulence transitions near the pedestal top for sustaining stationary I-mode. (30th September 2020) - Liu, A.D.; Zou, X.L.; Han, M.K.; Wang, T.B.; Zhou, C.; Wang, M.Y.; Duan, Y.M.; Verdoolaege, G.; Dong, J.Q.; Wang, Z.X.; Xi, F.; Xie, J.L.; et al.
Abstract: A reproducible stationary improved confinement mode (I-mode) has been achieved recently in the Experimental Advanced Superconducting Tokamak (EAST), featuring good confinement without particle transport barrier. The microscopic mechanism of sustaining stationary I-mode, based on the coupling between turbulence transitions and the edge temperature oscillation, has been discovered for the first time. A radially localized edge temperature ring oscillation (ETRO) with azimuthally symmetric structure ( n  = 0, m  = 0) has been identified and it is accompanied by alternating turbulence transitions between an electron diamagnetic drift turbulence (ET) and an ion diamagnetic drift turbulence (IT). The transition is controlled by local electron temperature gradient and strong non-linear couplings between weak coherent mode (WCM) and ET could be identified near the pedestal top, suggesting the unique status of the pedestal top region in sustaining the stationary I-mode confinement on EAST.